2003
DOI: 10.1046/j.1440-1746.2003.03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross appearance of hepatocellular carcinoma reflects E‐cadherin expression and risk of early recurrence after surgical treatment

Abstract: Types 2 and 3 HCC have marked metastatic and invasive potential and reduced expression of E-cadherin, predicting a high risk of recurrence after surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 13 publications
3
53
0
Order By: Relevance
“…24 In a variety of cancers, such as lobular breast carcinoma, diffuse gastric carcinoma, endometrial and ovarian carcinoma, and hepatocellular carcinoma, reduced expression of E-cadherin due to genetic mutations, in combination with loss of heterozygosity at the E-cadherin gene (CDH1), has been correlated with the disruption of cell-cell contacts, epithelialmesenchymal transition, invasiveness, and metastatic potential. 20,[25][26][27][28][29][30] In this study, hepatocytes in normal liver and in hepatocellular adenoma showed a uniformly high expression of E-cadherin. Hepatocellular carcinoma with cirrhosis had a significantly MMPs are a group of zinc-dependent endopeptidases that share many structural and functional properties, but have different substrate specificities.…”
Section: Discussionmentioning
confidence: 94%
“…24 In a variety of cancers, such as lobular breast carcinoma, diffuse gastric carcinoma, endometrial and ovarian carcinoma, and hepatocellular carcinoma, reduced expression of E-cadherin due to genetic mutations, in combination with loss of heterozygosity at the E-cadherin gene (CDH1), has been correlated with the disruption of cell-cell contacts, epithelialmesenchymal transition, invasiveness, and metastatic potential. 20,[25][26][27][28][29][30] In this study, hepatocytes in normal liver and in hepatocellular adenoma showed a uniformly high expression of E-cadherin. Hepatocellular carcinoma with cirrhosis had a significantly MMPs are a group of zinc-dependent endopeptidases that share many structural and functional properties, but have different substrate specificities.…”
Section: Discussionmentioning
confidence: 94%
“…25,26 This is the first study suggesting that inhibition of the TGF-␤1 pathway with LY2109761 may be a promising therapy in HCC patients, but more studies are needed to better define patients whose biological characteristics make them candidates for such a therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this adhesive function, E-cadherin has been suggested as an invasion suppressor molecule [10]. Since E-cadherin expression is inversely correlated with the degree of invasiveness in hepatocellular carcinoma [11], E-cadherin levels are considered as a potential biomarker of these tumors [12]. The epithelial-mesenchymal transition (EMT), a process in which epithelial cells acquire mesenchyme-like properties, is characterized by loss of E-cadherin and is associated with development and tumor progression.…”
Section: +mentioning
confidence: 99%